Kajian Yuridis Pemberhentian Periode Masa Jabatan Kepala Daerah - Ulahayanan, Antonius; Piris, Hendry John; Soplanit, Miracle (Jurnal Saniri, 2025)
Article 162 paragraphs (1) and (2) of Law Number 10 of 2016 concerning Regional Head Elections (Pilkada) stipulate that regional heads hold office for five years from the date of inauguration and may be re-elected only once for the same position. However, this provision gives rise to differing interpretations when Article 201 paragraphs (5) and (7) regulate the terms of office for regional heads elected in 2018 and 2020, which end in 2023 and 2024, respectively. This inconsistency has led to constitutional disputes, as seen in the lawsuit filed by several regional heads elected in 2018 but inaugurated in 2019 against Article 201 paragraph (5) of the Pilkada Law, which was partially granted by the Constitutional Court (Decision No. 143/PUU-XXI/2023), while a similar lawsuit against Article 201 paragraph (7) was entirely rejected in 2022. This study aims to analyze the legal validity of terminating the term of office of regional heads and its legal implications in the implementation of the 2024 simultaneous regional elections. The research employs a normative legal method with statutory and conceptual approaches. The results indicate that the termination of the regional heads’ term of office for the alignment of the 2024 simultaneous elections has binding legal force in accordance with existing legislation. The resulting legal implications include potential normative inconsistencies, challenges to legal compliance, impacts on the continuity of governmental programs, administrative adjustments, and effects on public trust.